(untitled) (LEARNing Landscapes, 2015)
The focus of this qualitative study is on three female teachers’ experiences as teacher researchers in the midst of conducting first-time research studies about their own teaching/professional practices. Inquiring into participants’ accounts of their research experiences revealed complex personal and professional obligations shaping the amount of time that participants felt able to invest in the research process. The findings of this paper have implications for better understanding teacher research as a sustainable professional learning endeavour and for considering the complexities teacher researchers must navigate as part of their professional development.